An assessment of heavy metal levels in brackish water shrimps: Impact on sexes and the relationship between metal pollution index and Fulton's K condition indices. Issue 8 (17th November 2019) - Mohamed Harris, Jalaldeen; Vinobaba, Periyathamby; Kularatne, Ranil Kavindra Asela; Kankanamge, Champika Ellawala
ABSTRACT: We examined the temporal variation of heavy metals in different sexes of three brackish water shrimp species with emphasis on the relationship between Fulton's K condition indices and metal pollution index (MPI). Zn was the most abundant metal followed by Sn, though levels were below the admissible limits (irrespective of gender). Temporal variation of Zn and Pb was significant ( p < 0.01). Drier weather conditions influenced Pb accumulation. Temporal variation of Sn was insignificant ( p > 0.05), but temporal variation of Hg was significant only in Penaeus monodon ( p < 0.0001). However, the relationship between temporal variation of the above-mentioned metals and gender was insignificant except in Penaeus semisulcatus for Pb ( p < 0.02) and Sn ( p < 0.04) despite no consistent higher bioaccumulation pattern by one particular sex. There were no significant negative correlations between the Fulton's K condition indices and MPI values in the different sexes. MPI values between the two sexes were insignificant. Any differences in the MPI values between the three species were insignificant. Only Penaeus semisulcatus exhibited significant differences ( p < 0.022) in Fulton's K condition indices in relation to gender. Fulton's K condition indices are unreliable indicators of metal-induced stress levels in shrimps.